Animal-type melanoma: dog or wolf? A review of the literature and a case report. (12th September 2018) - Stucci, Luigia Stefania; Palmirotta, Raffaele; Lovero, Domenica; Silvestris, Erica; Cafforio, Paola; Felici, Claudia; Todisco, Annalisa; Nacchiero, Eleonora; Pezzuto, Federica; Tucci, Marco; Silvestris, Franco
Abstract: The human animal type melanoma (ATM) is a rare subtype of melanoma characterised by the proliferation of pigmented dermal epithelioid and spindled melanocytes. However, this variant of melanoma is still lacking a precise nosography definition and classification for the difficulty to be distinguished from other more common melanocytic lesions, as well as for its peculiar biological behaviour. On the other hand, the contribution of scientific literature to this issue is fragmented and limited to the description of very few cases. Starting from the presentation of a case with abnormally aggressive clinical features, here we revisit the current knowledge on ATM from its dermatologic patterns, epidemiology, demography and histopathology to the clinical management. Peculiar accuracy has also been reserved to several histopathologic criteria, which are critical for the differential diagnosis from other melanocytic diseases in junction with molecular data deriving from recent cytogenetic and mutational characterisation of this tumour.